Recent trends and developments in conducting polymer nanocomposites for multifunctional applications - Sharma S.; Sudhakara P.; Omran A.A.B.; Singh J.; Ilyas R.A. (MDPI, 2023)
Actuators; Adhesives; Blending; Charge transfer; Composite materials; Conducting polymers; Corrosion resistant coatings; Cost effectiveness; Electric fields; Energy storage; Flexible electronics; Fossil fuels; Fuel cells; Fuel storage; Medical applications; Nanocomposites; Organic semiconductor materials; Polymer solar cells; Processing; Rare earths; Scratch resistance; Shape-memory alloy; Shape-memory polymer; Supercapacitor; Charge transfer complex; Conducting polymer composites; Conducting polymer nanocomposites; Electrically conducting polymer; Improved mechanical characteristics; Inorganic semiconductors; Optical and electrical properties; Organic electronic materials; Functional polymers